Genetic diversity estimates of Pinus pinaster in the Iberian Peninsula: a comparison of allozymes and quantitative traits - Gonzalez Martinez, S.C.=700 1 Gil, L.; Alia, R.
(En, Es)
ilus., 36 ref.
Keywords: MARCADORES GENETICOS; EXPERIMENTACCION EN CAMPO; VARIACION GENETICA; PINUS PINASTER; ESPAÑA